HUBUNGAN PENDIDIKAN DAN PENGETAHUAN WANITA DEWASA TERHADAP PERILAKU PENCEGAHAN KANKER PAYUDARA DAN KANKER SERVIKS DI LINGKUNGAN KELUARGA BINAAN KESEHATAN KELURAHAN TEGAL SARI MANDALA II - SACCA TIARA HARLIN; DWI MAYAHETI NASUTION (LP2MTBM MAKARIOZ, 2020)
Breast and cervical cancer is a major health problem in woman in the world and in Indonesia. Education factors and a lack ofpublic knowledge about breast and cervical cancer caused an increade in the incidence of this disease. The importance ofknowledge about breast an cervical cancer is expected so that people motivated to take preventive behavior and throughpreventive behavior are expected to reduce the incidence of breast and cervical cancer. To know the correlation betweeneducation and knowledge a woman toward prevented behaviorof breast and uterine cancer within the area of supervisedfamilies in Tegal Sari Mandala II. This study is descriptive of analytic with cross sectional design. Result: This study is usingKruskal-Wallis test. Test analysis of Kruskal-Wallis we get of P Value showed asym sig in correlation between education withprevented behavior of breast cancer (P Value=0.004), between knowledge with prevented behavior of breast cancer (PValue=0.008), between education with prevented behavior of uterine cancer (P Value=0.037). There is correlation betweeneducation with knowledge a woman prevented behavior toward prevented behavior of breast and uterine cancer within thearea of supervised families in Tegal Sari Mandala II.